Estabelecimento de parâmetros toxicológicos do imidacloprido, para a abelha sem ferrão Scaptotrigona sp. nov. - Gurgel, Leonardo dos Santos (2015)
Among the whole factors pointed as responsible for the loss of bee’s colonies, the crop protection products which belong to the chemical group of neonicotinoids deserve to be highlighted. Specially the systemic insecticides as imidacloprid which is an agonist acetylcholine and and acts on nicotinic acetylcholine receptors of insects, causing impairment of vital organ function and death. The currently job aimed to determinate the toxicity of imidacloprid by different exposition ways for stingless bees Scaptotrigona sp. nov. through the topical average lethal dose (DL50) and the intake average lethal concentration (CL50). It was conducted at Setor de Abelhas, Department of Animal Science at Federal University of Ceara and based on the international protocol of OECD. The mortality data was taken after 24 and 48 hours of exposition of the insects to different dosages and submitted to dose response analysis with Bioestat® version 5.3. The topical DL50 in ng p.c /µL/bee was 16,65 (24 hours) and 8,23 (48 hours), and the intake CL50 was 8,47 (24 hours) and 2,98 (48 hours) ng p.c /µL of food. The imidacloprid has shown to be toxic to the researched bee specie, been more harmfull when taken by oral ways, based on its minor lethal dose needed to kill 50% of the tested population.